Edukasi Pembuatan Biopori di Dusun Bulu Desa Mukuh Kecamatan Kayen Kidul Kabupaten Kediri - Supandji, Supandji; Wijaya, Galuh Adi; Addinandra, Fyan Faqih (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2022)
Bio-pores is one of the solutions to the problems faced when high-intensity rain conditions create a puddle to absorb water in an area more quickly. The purpose of this service were firstly to socialize the importance of drainage and handling of water runoff and secondly to provide training on making bio-pores, and thirdly, to manage integrated waste. The method used in carrying out this activity was the emancipatory participation method which allowed direct interaction by providing training and practicing activities. There were four stages of activity implementation: (1) Activity preparation, (2) Initial phase of socialization, (3) training application and practice, and (4) activity evaluation. The results of this activity were that the people of Bulu Hamlet and students at SDN Mukuh 2 enthusiastically participated in socialization on the importance of drainage and handling of water runoff. This service can also contribute by collaborating on manufacturing bio pores to reduce water runoff at 13 points in Bulu Hamlet.Biopori merupakan suatu metode yang digunakan untuk mengatasi permasalahan terhadap menurunnya daya serap air pada suatu wilayah. Tujuan dari pengabdian ini adalah pertama memberikan sosialisasi pentingnya drainase dan penanganan limpasan air, kedua memberikan pelatihan pembuatan biopori, dan ketiga, mampu mengelola sampah terpadu. Metode pelaksanannya memakai partisipasi emansipatoris, sehingga terjadi interaksi, komunikasi, dan dialog dengan warga melalui kegiatan pelatihan atau penyuluhan dengan 4 tahapan: (1) tahap persiapan, (2) sosialisasi pendahuluan, (3) pelaksanaan pelatihan dan praktek, dan (4) evaluasi. Hasil kegiatan ini adalah masyarakat Dusun Bulu dan Siswa SDN Mukuh 2 Antusias mengikuti sosialiasi pentingnya drainase dan penanaganan limpasan air. pengabdian ini juga mampu berkontribusi dengan melakukan kolaborasi pembuatan biopori untuk mengurangi limpasan air di 13 titik di Dusun Bulu.